Government Efforts to Prevent Potential Violence Against Women During the Covid-19 Pandemic in Indonesia - Devid Frastiawan Amir Sup (Universitas Islam Negeri Antasari Banjarmasin, 2021)
The implementation of large-scale social restrictions in Indonesia to prevent the wider spread of the Covid-19 pandemic, ultimately has socio-economic impacts, which then on a household scale also has the potential to cause violence in it. Women are those who are vulnerable to becoming victims of violence, especially during this pandemic. This research aims to describe the efforts taken by the government in Indonesia in preventing potential violence against women during the Covid-19 pandemic. This research uses qualitative-descriptive-textual methods. The results of this research are, to overcome these socio-economic impacts, the government has taken efforts through social safety net programs. Furthermore, to prevent the potential for violence against women during this pandemic, the government took the effort by implementing the Protocol on the Handling of Cases of Violence Against Women in the Covid-19 Pandemic Period. The value of this research are, to explain that the government has special attention to ensure the availability of protection services for victims of violence against women during this pandemic. Furthermore, through this research, the researchers invite together to work together in support of the efforts taken by the government to minimize the socio-economic impact of the Covid-19 pandemic, so that it can be resolved immediately.